Detecção de Salmonella sp. em aves silvestres cativas e avaliação do impacto sobre a avicultura - Luz, Patrícia Gaspar da (2012)
Salmonelosis is a term to designate patologies caused by the Salmonella genus, which has an extensive dissemination in the poultry environment and a large interconnection with wild birds, which act as reservoirs. Salmonella sp. is representative of the Enterobacteria s family, being usually associated with infections on aviary, and human food poisoning. It can, mainly in wild birds, present as asymptomatic form, which give to these animals the status of carrier and diffuser in the environment. The present research had the purpose to detect wild bird carriers of the agent, also by inoculation of the found strain in vivo, realize the retro isolation, so researching the effects caused on poultry production and evaluating its impact over the aviculture. The biological material that had been collected of the wild birds was derived of cloacal swabs, totalizing 121 samples of eleven different groups, which were processed by isolation. Only one from the 121 samples was positive, isolated in a Magellanic penguin (Spheniscus magellanicus), then was inoculated in chicks (Gallus gallus) with one day of age, which were challenged and watched for 12 days. In total 21 chicks were used as biological model, distributed in 3 groups, one positive control (inoculated with a known sample of Salmonella), one negative control (inoculated with saline solution), and one challenged with the strain field found and identified as Salmonella sp. After the observation period, was executed the sacrifice of the birds by full bleed, when were collected blood samples for serology, and the necropsy with collect of biological material of liver, duodenum, jejunum and cecum for bacteriological diagnosis, also histopathological. In the bacteriological diagnosis were found biochemical profiles compatibles with the bacteria in question both in the positive control group and in the group which was challenged with the strain field. After, the retro isolation was confirmed by the serological identification technique, in which there was an agglutination reaction of the standard serum with the retro isolated antigen from these two groups of birds. In the histopathology lesions caused by Salmonella sp. were observed in the studied organs, both in the positive control group and in the challenged group. Also it was possible to detect the presence of anti Salmonella sp. antibodies in the end of the experimental period in both groups of birds where was retro isolated the bacteria. So, even with the low isolation of the bacteria in the species of wild birds studied, there is the possibility of transmission of Salmonella sp. to poultry production, from strain of wild marine birds, and its potential to cause disease, and consequently, prejudice in the avian environment.